Relationship between Precipitation Just above the Lava Dome and Displacement of the Dome Using X-Band MP Radar at Unzen Fugendake - Rikuto Daikai; Christopher Gomez; Balazs Bradak; Norifumi Hotta; Yoshinori Shinohara (Proceedings)
Since its last eruption in 1990–1995, the Unzen volcano (Shimabara Peninsula, Japan) has been quiescent. At its summit, a complex dacitic dome spreads toward the East, in the direction of the Mizunashigawa valley. In a precarious equilibrium, sliding over previously erupted material, the dome has been generating rockfalls, and as the surrounding gullies have been eroding headward, the stability of the dome is further reduced. Even if the volcano is in a dormant stage, its monitoring is therefore essential for disaster risk management. Therefore, the present contribution aims to (1) quantify the minute dome movement as a whole as well as (2) when divided by lobe in order to understand deformation, and (3) calculate the link between rainfalls and the dome movement. The method relies on the Unzen GBSAR system (ground-based synthetic aperture radar system) and on 48-hour rainfalls from MP radar rain gauge stations at Unzen volcano. As a result, the authors have identified that: (1) there is a time delay between rainfall events and dome movements, and that peak rainfall alone is not sufficient to trigger dome movement; (2) the lower part of the dome rises and falls more rapidly than the upper part of the dome when rainfall is less than 100 mm/48 h; and (3) the upper and lower parts of the dome move up and down at the same level when rainfall exceeds 100 mm/48 h. In turn, when rainfall exceeds 250 mm/48 h, the upper part of the dome also displays a further downward movement, so that the entire dome might be moving down, similar to an accordion.